IMPLIKASI KECERDASAN DALAM PEMBELAJARAN PAI - Najmi Syakib (Universitas Islam Syekh-Yusuf, 2023)
Abstract The purpose of this study is to reveal the involvement of intelligence in learning that must be considered by the teacher so that the learning process can run according to the level of needs and abilities of students. Qualitative is the approach used in this study, while this type of research uses library research or literature study by reviewing several sources of books or literature as data samples. And the researcher in this study acts as an instrument in the research. The results of this study reveal the implications of intelligence in learning that must be applied by teachers as educational practitioners by providing services to students who focus on multiple intelligences by providing learning process facilities that support the development of their intelligence. The conclusion of this study reveals that intelligence and learning are two elements that are definitely involved in the learning process, because a person can be smart if he learns and someone can learn if he uses his intelligence to the fullest. Therefore the role of the teacher is very vital in providing learning that is implicated by intelligence. Keywords: Implications Intelligence, Learning PAI